2005
DOI: 10.1097/01.qai.0000167156.44980.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Efavirenz on the Pharmacokinetics of Simvastatin, Atorvastatin, and Pravastatin

Abstract: Efavirenz (EFV) is associated with hyperlipidemia when used in combination with other antiretroviral drugs. EFV is a mixed inducer/inhibitor of cytochrome P450 (CYP) 3A4 isozyme and may interact with hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase inhibitors that are primarily metabolized via CYP3A4. To assess the drug-drug interaction of EFV used in combination with simvastatin (SIM), atorvastatin (ATR), or pravastatin (PRA), an open-label trial was conducted in 52 healthy adult HIV-seronegative subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
3
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 20 publications
8
75
3
2
Order By: Relevance
“…The attenuated lipid response is not unexpected and most likely related to a reduction in pravastatin concentrations similar to the observations of Gerber and colleagues [7]. The mechanism by which the pravastatin concentrations may decrease with coadministration of EFV has yet to be fully elucidated.…”
Section: Pi-based ---------------------------------------------------supporting
confidence: 57%
See 2 more Smart Citations
“…The attenuated lipid response is not unexpected and most likely related to a reduction in pravastatin concentrations similar to the observations of Gerber and colleagues [7]. The mechanism by which the pravastatin concentrations may decrease with coadministration of EFV has yet to be fully elucidated.…”
Section: Pi-based ---------------------------------------------------supporting
confidence: 57%
“…This study showed that the AUC of simvastatin acid was reduced by -58% (p = 0.003), the AUC of atorvastatin with active metabolites was reduced by -34% (p<0.001) and that the AUC of pravastatin was reduced by -40% (p = 0.005). While they did report an observed attenuation of LDL lowering with EFV with 4 days of statin use, these results were only statistically significant for the simvastatin arm nor do they reflect the effect that chronic concurrent administration used in real-world clinical practice might have on LDL-lowering efficacy [7]. The present study differs from this pharmacokinetic study in that we evaluated the lipid lowering efficacy and safety of pravastatin in both HIV-infected patients on NNRTI and PI-based HAART and after being on stable doses of the statin for at least 4 weeks to reflect a more clinically relevant scenario.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Co-administration of efavirenz (600 mg) with either simvastatin (40 mg once daily), atorvastatin (10 mg once daily), or pravastatin (40 mg once daily) resulted in significant reductions in the area under the curve (AUC) at 0 to 24 hours for all 3 statins: 58% reduction for simvastatin, 43% for atorvastatin, and 40% for pravastatin. 29 A separate study found that patients on an efavirenz-based ARV regimen who …”
Section: Potential Drug Interactions With Artmentioning
confidence: 99%
“…35,49 Co-administration of the NNRTI efavirenz with simvastatin, atorvastatin, or pravastatin can result in significant induction of statin metabolism. 55 The reduced inhibition of HMG-CoA reductase activity during co-administration of efavirenz may result in diminished antilipid efficacy at usual doses, and statin dosages may need to be cautiously increased. Unlike PIs, NNRTIs, and cobicistat, raltegravir has no inhibitory or inductive potential in vitro.…”
Section: Ncep-atp III Ldl-c Goal Modifying Risk Factors (Exclusive Ofmentioning
confidence: 99%